Optimization of hydraulic efficiency of a free surface semicircular breakwater using wave screens - Teh, H.M. (American Society of Mechanical Engineers (ASME), 2015)
A free surface semicircular breakwater (SCB) with rectangular perforations has been developed to serve as a wave defence structure. Hydrodynamic performance of the breakwaters of various perforations has been thoroughly investigated through wave measurements in a wave flume under random waves. The SCBs were experimentally confirmed to be good anti-reflection wave structures; however, the level of wave transmission at the leeside of the SCBs was rather high particularly when immersed in limited depth and confronted by waves of longer period. This study aims at optimizing the hydraulic characteristics of the SCB by extending its draft by means of wave screens. Three test configurations have been identified in this study, namely (1) the SCB with front screen, (2) the SCB with rear screen, and (3) the SCB with double screens. For each wave screen, three porosities (i.e. 25, 40 and 50) have been considered in the experiments. The models of shallow immersion depths have been tested in random waves of different characteristics in a wave flume. Wave transformation at different locations upstream and downstream of the test models has been recorded by wave probes. The hydraulic performance of the breakwater are quantified by the coefficients of wave transmission, reflection and energy dissipation, and the wave climate in the vicinity of the breakwater are presented in the form of a ratio relative to the incident wave height. The optimum design of SCB supplemented by truncated wave screen(s) is proposed at the end of the study. Â© 2015 by ASME.